2021
DOI: 10.1007/s11207-021-01938-7
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Solar Magnetic Activity: 140 Years of the ‘Extended Solar Cycle’ – Mapping the Hale Cycle

Abstract: We investigate the occurrence of the “extended solar cycle” (ESC) as it occurs in a host of observational data spanning 140 years. Investigating coronal, chromospheric, photospheric, and interior diagnostics, we develop a consistent picture of solar activity migration linked to the 22-year Hale (magnetic) cycle using superposed epoch analysis (SEA) and previously identified Hale cycle termination events as the key time for the SEA. Our analysis shows that the ESC and Hale cycle, as highlighted by the terminato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…First identified in M2014, then discussed in M2019 (and with broader observational context in McIntosh et al, 2021) we introduced the Hale Cycle termination event, or 'terminator' . In the previous section we discussed the progression of Hale Cycles, inferring that they interact with one another to shape the magnetic activity that we experience.…”
Section: What Is the Terminator?mentioning
confidence: 99%
See 1 more Smart Citation
“…First identified in M2014, then discussed in M2019 (and with broader observational context in McIntosh et al, 2021) we introduced the Hale Cycle termination event, or 'terminator' . In the previous section we discussed the progression of Hale Cycles, inferring that they interact with one another to shape the magnetic activity that we experience.…”
Section: What Is the Terminator?mentioning
confidence: 99%
“…At the terminator the frequency of sunspot growth at mid-latitudes rises dramatically and the polar reversal process commences at ±55°latitude (see also Dikpati et al, 2019). For the next period of time, the "ascending phase", sunspots grow in number almost linearly on the two mid-latitude Hale Cycle bands until, about the time that the polar reversal process completes and the polar coronal holes close (McIntosh et al, 2021), when the solar hemispheres reach their maximum sunspot number-i.e. "solar maximum".…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the solar magnetic field undergoes a magnetic polarity reversal each Schwabe cycle is intrinsically linked to the concept of an 'extended solar cycle' (Cliver 2014). In this extended picture, solar magnetic activity coherently originates at high latitudes (∼ 55 • ) and migrates equatorward over nearly two decades (e.g., Wilson et al 1988;McIntosh et al 2021). About a decade after leaving high latitudes the pattern gives rise to the familiar 'butterfly diagram' of sunspot latitudes (Maunder 1904).…”
Section: Introductionmentioning
confidence: 99%
“…One of these auxiliary observatories was the COI (Leonardo et al 2011). Some examples of recent studies using data from the Meudon Observatory are Mazumder et al (2021) and McIntosh et al (2021).…”
Section: Filament Numbermentioning
confidence: 99%
“…In the past several years, because of the recent digitization of historical solar records made in observatories around the world, we have improved our understanding of past solar activity. In the case of the solar prominences and filaments, for example, Tlatov et al (2016) analyzed the spatial and temporal evolution of solar filaments for the period 1919-2014 using data from the Meudon Observatory and the Kislovodsk Mountain Astronomical Station, whereas McIntosh et al (2021) showed from filament records made in Arcetri, Meudon, and Kislovodsk that the Hale magnetic cycle has been strongly recurrent since 1880. Chatterjee et al (2020) studied the latitude distribution of prominences for 10 solar cycles (Solar Cycle 15-24) from data recorded at the observatories of Kodaikanal, Meudon, and Kanzelhohe, and Carrasco et al (2019) Some historical sunspot catalogs by professional observatories, including records on different solar parameters such as latitudes and areas, have been also digitized.…”
Section: Introductionmentioning
confidence: 99%